2005
DOI: 10.1002/lt.20459
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and survival of patients with portopulmonary hypertension

Abstract: It is not known whether patients with pulmonary arterial hypertension associated with portal hypertension (portopulmonary hypertension (PPHTN) have different disease characteristics from those of patients with other forms of pulmonary arterial hypertension. We performed a retrospective cohort study of patients with PPHTN and patients with pulmonary arterial hypertension that was idiopathic, familial, or associated with anorexigen use (IPAH) to determine whether hemodynamics or survival were different between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
92
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(101 citation statements)
references
References 21 publications
5
92
0
4
Order By: Relevance
“…The management of POPH includes different classes of drugs, such as prostacyclin analogues, endothelin receptor antagonists, and PDE5 inhibitors. Recent data show that sildenafil has the advantage of being an oral compound with pulmonary vaso-selective action, but no hepatotoxicity [68,69]. OLT is a potentially curative therapeutic option for POPH patients.…”
Section: Portopulmonary Hypertensionmentioning
confidence: 99%
“…The management of POPH includes different classes of drugs, such as prostacyclin analogues, endothelin receptor antagonists, and PDE5 inhibitors. Recent data show that sildenafil has the advantage of being an oral compound with pulmonary vaso-selective action, but no hepatotoxicity [68,69]. OLT is a potentially curative therapeutic option for POPH patients.…”
Section: Portopulmonary Hypertensionmentioning
confidence: 99%
“…Pre-capillary PH occured in approximately 40%-45% of those with PH in SCD. 14,18 This prevalence would place SCD-PH as second only to scleroderma (12%) among associated conditions under World Health Organization (WHO) group I PAH, 21 and comparable to portopulmonary hypertension (1% to 6%), 22 25 The classification of SCD-PH has evolved during the successive PH world meetings: In the Evian classification, 26 it was placed in Group IV, in the Venice and Dana Point, 27 it was shifted to Group I and in the Nice classification, it was shifted to Group V. 25 The reclassification of SCD-PH as Group IV, Group I, and now as Group V stresses the need to define PH subgroups and conduct further research in these patients. 24 …”
Section: Introductionmentioning
confidence: 99%
“…We have read the article of Kawut et al 1 about survival of patients with portopulmonary hypertension (PPHTN) and would like to refer a patient with chronic liver failure in Child-Pugh C stage and severe portopulmonary hypertension with successful treatment with sildenafil.…”
mentioning
confidence: 99%
“…Kawut et al 1 found that patients with PPHTN have a greater risk of death than that of idiopathic pulmonary arterial hypertension even after controlling for differences in liver function or therapeutics approach. However, the proportion of patients with treatment is low (only one patient with bosentan and none with sildenafil).…”
mentioning
confidence: 99%
See 1 more Smart Citation